PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CONSTRUCT TWO PADA TEMA 2 SELALU BERHEMAT ENERGI SUBTEMA 1 KELAS IV SD - Arie Widya Murni; Miftahul Jannah (Jurnal Muassis Pendidikan Dasar, 2022)
This study discusses the development of interactive learning media based on construct two on theme 2 always saving energy in sub-theme 1 for fourth grade elementary school. This study aims to produce interactive learning media on theme 2 always save energy in sub-themes 1 learning 1 and 3. This type of research uses development research with the research model used is the 4-D model. This model consists of 4 stages of development, namely Define, Design, Develop, and Disseminate. However, due to the limitations of the research, the researchers conducted research up to the Develop stage only, which was to become 3-D. The object in this research is an interactive learning media based on Construct Two. The learning media developed in this study were validated by 2 validators. The results of the feasibility test of interactive learning media based on the assessment: 1) The media expert validator got 80% results which were included in the "very good" category. 2) Material expert validators get 91% results which are included in the "good" category. Thus the developed interactive learning media is declared suitable for use in learning